Perkembangan Penulisan Ilmiah Berkaitan Sifat 20 Di Malaysia: Satu Sorotan - Abdullah, Mohd Azman; Engku Alwi, Engku Ahmad Zaki (IAIN Samarinda, 2018)
This article aims to know how far the development of scientific writing related to Sifat 20 in Malaysia, particularly in the Jawi scriptures used in the teaching and learning in Pesantren. Therefore, this study observes the aqeedah books in Jawi’s writing which discuss Sifat 20. This article tries to reveal the approaches used by the ulama in Nusantara when discussing the chapter on believing in Allah SWT. This article examines the manuscripts of Jawi which discuss Sifat 20 and analyses the thoughts of Ulama in Nusantara related to Sifat 20. This study implements the content analysis methods, that is, by examining the texts or manuscripts in Jawi writing. The resuls of the study, based on the findings all the Jawi manuscripts written by Ulama in Nusantara, show that all of them adhered to the school of al-Asya’irah and al-Maturidiyyah which explains Sifat 20. The results of this study are expected to contribute future researchers in examining Sifat 20 and to enrich the scientific treasures, particularly in the field of aqeedah.